INNOVATIVE TEACHING TECHNOLOGIES IN HIGH SCHOOL - Осипенко, О. Ю. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2014)
The approaches to the formation of modern innovative technologies for training in high school are considered and the effectiveness and creativity of the current system of higher technical education are analyzed in the article